A new low-temperature firable 0.95Pb(ZrxTi1-x)O3-0.05Bi(Mn1/2Ti1/2)O3 ceramic for high-power applications. Issue 5 (1st April 2018) - Zhang, Bo; Qi, He; Zuo, Ruzhong
Abstract: A new ternary solid-solution piezoelectric ceramic of 0.95Pb(Zrx Ti1−x )O3 −0.05Bi(Mn1/2 Ti1/2 )O3 ( x = 0.49–0.55) was successfully prepared via a conventional solid-state reaction. The crystal structure was found to gradually transform from tetragonal to rhombohedral phases with increasing the Zr/Ti ratio. A morphotropic phase boundary was realized in the proximity of x = 0.51, which exhibited optimum electromechanical properties of d33 = 275 pC/N, ε33 T /ε0 = 1226, kp = 0.53, Qm = 1164, tanδ = 0.66% and Tc = 341 °C as sintered at a relatively low temperature of 1120 °C. Compared with typical Pb-based complex perovskites such as Pb(Mn1/3 Nb2/3 )O3 and Pb(Mn1/3 Sb2/3 )O3, the substitution of Bi(Mn1/2 Ti1/2 )O3 provides obvious advantages in both sintering temperature and raw material cost. The achievement of piezoelectric and electromechanical properties was interpreted by means of a typical model concerning the interaction between defect dipoles and domains through comparative experiments. The desirable properties of the studied material system suggest a great potential for high-power device applications.